A New Philosophy for International Law - DWORKIN, RONALD (Philosophy & public affairs, 2013)
As many philosophers have pointed out, there is mystery in the bare assumption that promising creates obligation. How can an individual change his moral situation just by speaking a runic phrase? If we want to explain why promises do create moral obligations, we must point to different, more basic moral principles that a promise invokes. Philosophers have suggested a variety of such principles. We must look for similar, more basic principles within international law. Dworkin posits that if law is understood as a special part of political morality, and if it serves its community well, its doctrines will crystallize over time. Its roots in political morality will grow less prominent--though will be available when needed--in ordinary legal argument.